Determination of seasonal factors for structural condition values of bituminous pavements - Puodžiukas, Virgaudas; Pakalnis, Algis (Journal of Civil Engineering and Management, 2002)
This article studies the effect of each season on the structural condition values of bituminous pavements. Testing of bituminous pavements was carried out by the falling-weight deflectometer DYNATEST 8000. FWD. The following values of pavement strength were used: the equivalent resilient modulus of the road pavement Eekv; deformation modulus of the roadbed soil Eg; pavement structural number SN; subgrade structural number SNSG; a modified structural number SNC. In the process of work the structural condition values of spring and autumn were determined and a statistical analysis of these values was presented. The analysis of the three-year research results showed that in spring the pavement condition weakens in respect of all criteria of pavement structural condition. Therefore, for the future analysis only the structural condition values of spring are suggested to be used. The article gives also the critical period adjustment factors for each structural condition value on the selected test road sections with different pavement structure. The article gives recommendations for the practical use of research results.Frist Published Online: 30 Jul 2012